APPLICATION OF LIQUID ORGANIC FERTILIZER AND NPK BLUE ON THE GROWTH OF PEANUT (Arachis hypogea L.) - Nico Syahputra Sebayang; Syariani Tambunan; Suhadi Suhadi (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2022)
Peanuts make a significant contribution in meeting the needs of legumes, especially in Southeast Aceh Regency. This research was conducted in Kisam Village, Bambel District, Southeast Aceh, with an altitude of ± 220 m above sea level. The aim of the study was to determine the application of liquid organic fertilizer and the dose of NPK fertilizer on the growth and development of peanut (arachis Hypogea L.) plants. The design used in this study was a Randomized Block Design (RAK) which was arranged in a factorial manner with 9 treatment combinations with 3 (three) replications. The treatment consisted of 2 (two) factors, namely the first treatment of liquid organic fertilizer (P1) 2cc/l water, (P2) 4 cc/l water and (P3) 8 cc/l water, while the second factor was the dose of NPK fertilizer (N1 ) 1.25 g/plant, (N2) 1.75gr/plant and (N3) 2.25 g/plant. The observed variables were plant height, number of branches, number of petioles and number of leaves. The results showed that the application of liquid organic fertilizer (P1) gave the best results on plant height, number of branches, number of petioles and number of leaves. Dosage of NPK (N3) fertilizer gave the best results on plant height, number of leaves. The interaction of treatment with liquid organic fertilizer (P1) and dose of NPK fertilizer (N3) gave the best effect on the growth and production of peanut plants. The results of the analysis of variance showed that there was no significant interaction between the treatment of giving liquid organic fertilizer (Pocnasa) and chemical fertilizer (NPK Biru) to all observed variables.